Essays on the effectiveness of KAM disclosure in auditor's reports - Rematzki, Johanna (Technische Universität Dortmund, 2018)
This cumulative dissertation examines the effectiveness of key audit matters (KAMs) in the auditor’s report. The first paper investigates whether KAMs contribute to the audit expectation gap. While standard setters and regulators suggest that the expanded auditor's report will be a lot clearer when KAM disclosure is included, researchers believe that the audit expectation gap is rather an educational gap which exists because financial statement users are not aware of auditor’s responsibilities, even in the presence of KAMs. Our results reveal that KAM disclosure may not serve as a beneficial tool to narrow the audit expectation gap. The second paper examines the effect of linguistic characteristics in KAM disclosure on investors’ behavior in two ways: investors’ tendency to scrutinize managerial decision-making and investors' willingness to invest. While our findings show no significant differences for investors’ tendency to scrutinize managerial judgment making, we find that investors receiving an auditor's report with firm-specific information are less willing to invest in the company than investors who received an auditor’s report with standardized language. The third paper examines whether KAM disclosure influences managerial decision-making. We provide evidence that managers engage less in earnings management activities when the level of transparency in the auditor’s report increases. The fourth paper analyzes expanded auditor’s reports of CDAX listed companies in Germany. Our results show that the auditor identifies a wide variety of accounting matters in KAM disclosure which increases the informational value of the “new” auditor’s report. However, we also find that boilerplate and standardized language still exists. Taken together, the dissertation sheds light on the potential costs and benefits of KAM disclosure in the auditor’s report.
Keywords: Key Audit Matters; Auditor's report; Investors' behavior; Audit expectation gap; Financial reporting environment; 330; Prüfungsbericht; Anlageverhalten; Finanzberichterstattung; Offenlegung